Effects of platelet-rich plasma on healing of alveolar socket: Split-mouth histological and histometric evaluation in Cebus apella monkeys - Pessoa Roberto; Oliveira Sergio; Menezes Helder; de Magalhaes Denildo (Wolters Kluwer Medknow Publications, 2009)
Context: The prediction of implant treatment is directly influenced by the quality of the remaining bone after tooth extraction. Aims : The purpose of this experimental study was to, histologically and histometrically, evaluate the bone repair process in the central areas of extraction sockets filled with platelet-rich plasma. Materials and Methods: Four young adult male Cebus apella monkeys were used. The extraction of both right and left inferior second premolars was accomplished. After extraction, in one of the extraction sockets, coagulum was maintained while in the other it was removed; the alveolus was dried with gauze compress and filled up with platelet concentrate. For PRP production, Sonnleitner′s protocol was followed. The specimens for histological and histometric assessment were obtained in 30, 90, 120 and 180 days intervals. Results: In 30 days new bone formation was intense in both experimental and control sockets and no significant differences were observed between the two groups. After 90 days of the extraction, while the control group showed signs of decrease in osteogenesis, in the experimental unit, the process of bone formation and fibroblast-like cell proliferation remained intense. After 120 days, the PRP treated socket was occupied by large trabeculae of bone. After 180 days, the control unit was occupied mostly with bone marrow. The experimental unit remained occupied with large amounts of bone tissue. Conclusions: It was possible to conclude that bone repair was enhanced by the use of platelet- rich plasma in alveolar sockets.